Patterns of Musculoskeletal Disorders among Staff Nurses in the Emergency Department in Saudi Arabia: A Cross-sectional Study - Alrimali, Afaf Mufadhi; Alreshidi, Nashi Masnad; Alshammari, Aljazi Albshri; Alenzy, Aeedah Rfadah; Thomas, Riya; Dinoy, May Ann; Alanzi, Fouz Aziz; Pasay-an, Eddieson (Nurse Media Journal of Nursing, 2024)
Background: The physically demanding and high-stress environment of Emergency Departments (EDs) significantly contributes to the heightened risk of musculoskeletal disorders (MSDs) among ED nurses. Despite this known association, there is a lack of comprehensive understanding of the prevalence rates and contributing factors within ED settings in Saudi Arabia, necessitating further investigation.Purpose: This study delves into the prevalence and potential predictors of MSDs among nurses in this critical healthcare setting.Methods: A cross-sectional survey was conducted in March 2023 using convenience sampling of 177 ED nurses across 16 public hospitals in Hail, Saudi Arabia. The Nordic Musculoskeletal Questionnaire was employed, with SPSS analyses covering frequency and percentage of pain prevalence via cross-tabulation, and logistic regression to identify risk factors.Results: Over the past year, 68.9% of participants reported lower back pain affecting normal activities in 55.4% of cases. Neck pain was more likely in individuals aged 20-29 and former smokers accounting for 47.6% of the variance (p=0.001). Shorter shifts under 8 hours reduced neck pain risk, whereas a schedule with 50% of night shifts heightened the risk, contributing to 28.4% of the variance (p=0.001). Nurses aged 40-49 and those with significant childcare duties faced higher shoulder pain risk (p=0.024), and adult caregiving duties was linked to upper back pain explaining 40.6% of the variance (p=0.017). No significant links were found for other musculoskeletal pains.Conclusion: The study reveals a significant prevalence of MSDs among the evaluated ED nurses, significantly influenced by specific demographic and work-related factors. Addressing these through ergonomic interventions, optimal scheduling, and wellness programs is crucial for nurse well-being and patient care. Future research should focus on creating holistic wellness programs that support nurses musculoskeletal health.